'To Decolonise': Where to, the Humanities?. Issue 1 (2nd January 2019) - Chapman, Michael
Abstract : Given demands in South Africa 'to decolonise', I argue that to decolonise is more complex and challenging than currently constitutes the discourse of decolonisation, either in South Africa or the globe. Focusing on the Humanities, more specifically on literature – with reference to Ngũgĩ's 'Nairobi Literature Debate' of the late 1960s – I frame discussion 'in-between' two significant gatherings, Bandung (1955) and the 10th BRICS Summit (2018), the former identified by Robert JC Young and Walter Mignolo as a marker in both postcolonial and decolonial 'theory'; the latter, in a shift between an earlier ideology-speak and the trade-investment speak of the Fourth Industrial Revolution. What might be the consequence of such an in-between space for research, teaching and curriculum design?